Islamic Tarbiyah System for Bullying Prevention - Amran Abdul Halim; Walid Mohd Said; Amiruddin Mohd Sobali; Abdulloh Salaeh; Nidzamuddin Zakaria; Norazmi Anas; Mohamad Qamarulzaman Mohamad Zani (Human Resource Management Academic Research Society, 2024)
Indexed by ERA